Non-destructive detection of protein content in mulberry leaves by using hyperspectral imaging - Li, Xunlan; Peng, Fangfang; Wei, Zhaoxin; Han, Guohui; Liu, Jianfei (Frontiers in Plant Science, 2023)
Protein content is one of the most important indicators for assessing the quality of mulberry leaves. This work is carried out for rapid and non-destructive detection of protein content of mulberry leaves using hyperspectral imaging (HSI) (Specim FX10 and FX17, Spectral Imaging Ltd., Oulu, Finland). The spectral range of HSI acquisition system and data processing methods (pretreatment, feature extraction and modeling) are compared. Hyperspectral images of three spectral ranges in 400–1000 nm (Spectral Range I), 900-1700 nm (Spectral Range II) and 400–1700 nm (Spectral Range III) were considered. With standard normal variate (SNV), Savitzky-Golay first-order derivation and multiplicative scatter correction used to preprocess the spectral data, and successive projections algorithm (SPA), competitive adaptive reweighted sampling and random frog used to extract the characteristic wavelengths, regression models are constructed by using partial least square and least squares-support vector machine (LS-SVM). And the protein content distribution of mulberry leaves is visualized based on the best model. The results show that the best results are obtained with the application of the model constructed by combining SNV with SPA and LS-SVM, showing R2 of up to 0.93, RMSE of just 0.71g/100g, and RPD of up to 3.83 based on HSI acquisition system of 900-1700 nm. The protein content distribution map of mulberry leaves show that the protein of healthy mulberry leaves distributes evenly among the mesophyll, with less protein content in the vein of the leaves. The above results show that rapid, non-destructive and high-precision detection of protein content of mulberry leaves can be achieved by applying SWIR HSI acquisition system combined with SNV-SPA-LS-SVM algorithm.